Preparation of ZnO/Al2O3 catalysts by using atomic layer deposition for plasma-assisted non-oxidative methane coupling - Jeong, Myung-Geun; Kim, Young Dok; Park, Sunyoung; Kasinathan, Palraj; Hwang, Young Kyu; Chang, Jong-San; Park, Yong-Ki (Journal of the Korean Physical Society, 2016)
We prepared a ZnO/mesoporous Al 2 O 3 -shell/core structure by using atomic layer deposition (ALD) of ZnO on commercially-available mesoporous Al 2 O 3 . We used various analysis techniques such as scanning and transmission electron microscopy, X-ray photoelectron spectroscopy, inductively coupled plasma-atomic emission spectroscopy, and surface area and pore size analyses based on nitrogen isotherm data. A 200 nm-thick slab of mesoporous Al 2 O 3 particles was decorated by ZnO upon ALD deposition, whereas the inner part of the Al 2 O 3 particle was free of ZnO. We evaluated the catalytic activity of the bare and the ZnO-covered Al 2 O 3 for plasma-assisted nonoxidative coupling of methane. The catalytic behavior was shown to be sensitive to the amount of ZnO deposited. Particularly, 40-cycled ZnO/Al 2 O 3 showed an enhanced selectivity to the olefin product with almost the same CH4 conversion as that of bare Al 2 O 3 . Preparation of the shell/core structure by using ALD can be an interesting strategy for finding highly-efficient catalysts in a plasma-assisted catalytic reaction.